Band tail interface states and quantum capacitance in a monolayer molybdenum disulfide field-effect-transistor. (24th January 2018) - Fang, Nan; Nagashio, Kosuke
Abstract: Although MoS2 field-effect transistors (FETs) with high- k dielectrics are promising for electron device applications, the underlying physical origin of interface degradation remains largely unexplored. Here, we present a systematic analysis of the energy distribution of the interface state density ( D it ) and the quantum capacitance ( C Q ) in a dual-gate monolayer exfoliated MoS2 FET. The C Q analysis enabled us to construct a D it extraction method as a function of E F . A band tail distribution of D it with the lowest value of 8  ×  10 11 cm −2 eV −1 suggests that D it is not directly related to the sharp peak energy distribution of the S vacancy. Therefore, the Mo–S bond bending related to the strain at the interface or the surface roughness of the SiO2 /Si substrate might be the origin. It is also shown that ultra-thin 2D materials are more sensitive to interface disorder due to the reduced density of states. Since all the constituents for the measured capacitance are well understood, I–V characteristics can be reproduced by utilizing the drift current model. As a result, one of the physical origins of the metal/insulator transition is suggested to be the external outcome of interface traps and quantum capacitance.